PENERAPAN MODEL COOPERATIVE LEARNING TIPE CO-OP CO-OP DISERTAI METODE EKSPERIMEN UNTUK MENINGKATKAN AKTIVITAS DAN HASIL BELAJAR SISWA KELAS VIII PADA MATERI TEOREMA PYTHAGORAS DI SMP NEGERI 2 RAMBIPUJI TAHUN PELAJARAN 2012/2013 - Dewi, D; Sugiarti, Titik; Suharto, S (Department of Mathematics Education , University of Jember, 2013)
Abstract. The goals of this research were: (1) to describe the application of cooperative learning model by co-op co-op type with experiment method to increasethe activity and the result of student learning at 8th Junior High School 2 Rambipuji; (2) to describe the improvement of students learning activitiesat 8th Junior High School 2 Rambipuji; (3) to describe improvement of achievement at 8th Junior High School 2Rambipuji. The type of this research was Classroom Action Research. The research methodology of this study used Hopkins scheme model which is spiral shaped. Data collection method of this research used observation, documentation, interview, and test. The data analysis used: (1) the percentage of students learning activities; (2) the percentage of achievement. This research was done through two cycles and there was two meeting in every cycle. The percentage classically of achievement in first cycle was 84,09%. The percentage of students learning activities at first cycle was 72,21% and it involved in active category. In the second cycle, percentage classically of achievement was coming high become 86,36% and the percentage of students learning activities at second cycle was 75,81% and it involved in active category. Key Words : Cooperative Learning Model, Co-op Co-op Type, Experiment Method